The validity and reliability of a biometrically accurate, photorealistic set of young adult body size scales based on 3D scans of White Europeans - Bethany J. Ridley; Piers L. Cornelissen; Robin S. S. Kramer; Nadia Maalin; Sophie Mohamed; Martin J. Tovée (PLoS ONE, 2026)
Young adults are a high-risk group for weight-related health problems but are often overlooked in weight management intervention design. Validated visual tools that accurately depict body size are needed to improve communication and intervention strategies. This study validated innovative, photo-realistic, gender-specific body size scales of young adults (aged 18), created from 3D scans to depict systematic changes in adiposity. A total of 110 young adults (aged 18–25) completed two behavioural tasks: (1) estimating the relative size of the bodies and (2) ranking them in ascending order of weight. To assess reliability, participants repeated the tasks three days later. Participants accurately estimated relative body sizes and ranked the images in line with the systematic BMI changes across the scales. Test–retest analyses showed good to excellent reliability for both tasks. The young adult body size scales are anthropometrically accurate, reliable, and valid tools for body size estimation tasks. They provide a robust resource for research, clinical communication, and intervention design focused on young adults.